2021
DOI: 10.1093/abbs/gmab012
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits necroptosis by mediating the TNF-α/RIP1/RIP3/MLKL pathway in myocardial hypoxia/reoxygenation injury

Abstract: Resveratrol (RES) protects myocardial cells from hypoxia/reoxygenation (H/R)-caused injury. However, the mechanism of this effect has not been clarified. Thus, in this study, we aimed to determine whether RES attenuates H/R-induced cell necroptosis by inhibiting the tumor necrosis factor-alpha (TNF-α)/receptor-interacting protein kinase 1 (RIP1)/RIP3/mixed-lineage kinase domain-like (MLKL) signaling pathway. Rat myocardial ischemia/reperfusion (I/R) models and H/R-injured cell models were constructed. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…As the RIP1/RIP3 pathway is a significant signaling pathway which is responsible for regulating cell viability and necroptosis in renal IRI 22 , TNFα is a classic inflammatory cytokine, but a familiar inducer of necroptosis in some pathological process, particularly in the disease containing inflammation and necrosis 23 . Inhibition of caspase8 can also induce necroptosis of renal tubular epithelial cells 17 .…”
Section: Resultsmentioning
confidence: 99%
“…As the RIP1/RIP3 pathway is a significant signaling pathway which is responsible for regulating cell viability and necroptosis in renal IRI 22 , TNFα is a classic inflammatory cytokine, but a familiar inducer of necroptosis in some pathological process, particularly in the disease containing inflammation and necrosis 23 . Inhibition of caspase8 can also induce necroptosis of renal tubular epithelial cells 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results showed that the levels of RIPK3, RIPK1 and MLKL were promoted during progression of ARHL. Previous, Hu et al revealed that RSV suppresses necroptosis in H9c2 cells, which may realize through the inhibition of the TNF-α/RIP1/RIP3/MLKL signaling pathway ( Hu et al, 2021 ). Consistently, our data depicted that the protein expressions of RIPK1, RIPK3, and MLKL in cochlea tissues were sharply decreased after administration of 50 mg/kg RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumor necrosis factor- α (TNF- α ) has been reported to play a key role in the initiation of necrosis and the induction of stimulated necrosis. TNF- α can activate cell suicide mechanisms, such as apoptosis and necrosis, and trigger the accumulation and phosphorylation of RIPK1 and RIPK3, resulting in the phosphorylation of MLKL, the formation of necrotic bodies, and necrosis [ 30 ]. Moreover, recent studies have identified that the elevated levels of necroptosis is accompanied by an increase in pro-inflammatory cytokines IL-6 and TNF- α (3.9-4.7-fold) in addition to an increase in the level of oxidative stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%